UKURAN TUBUH DAN STATUS FISIOLOGIS KAMBING PERAH SAANEN (KASUS DI PETERNAKAN INDO NATUTAL FARM SUKABUMI) - Aziz, Balqis Aulia; Taripin, Didin Supriat; Mutaqin, Bambang Kholiq (Faculty of Animal Husbandry, Universitas Padjadjaran, 2025)
Livestock productivity is affected by environmental and genetic factors. This study identifies body measurements and physiological status of Saanen dairy goats at Indo Natural Farm, Sukabumi, using a descriptive quantitative method with a census approach. The population included males and females in three age categories: <1 year, 1–2 years, and >2 years. Body measurements, body length (BL), heart girth (HG), and withers height (WH)—were recorded by sex and age. In general, most goats met the Indonesian National Standard (SNI 7352-4:2022). However, 4–5 month and 18-month-old bucklings, as well as 18-month-old does, showed body measurements below the minimum standard. At 24 months, only body length in does fell below standard. Physiological parameters, including rectal temperature (kids: 39.4 °C; adults: 39.0 °C), respiratory rate (kids: 37 breaths/min; adults: 37 breaths/min), and heart rate (kids: 95 bpm; adults: 88 bpm), remained within normal ranges, indicating no heat stress. These findings suggest that while most Saanen goats meet body measurement and physiological standards, targeted improvements may be needed for specific age groups to optimize growth and productivity.Keywords: body size, physiological status, diary goats, saanen goat, invirontmental factors